Aspects of mathematical preparation of future primary school teacher - Olkhova, Nataliia; Olkhova, Nastya (Східноєвропейський національний університет імені Лесі Українки, 2017)
Based on the analysis of scientific-methodical literature and work experience at university the article deals with the actual problem of preparing primary school teacher in teaching Mathematics. The reasons of insufficient mathematical teacher preparation of this direction were highlighted and the way of future improvement this process was described. The author emphasized the priority provisions of methodological-mathematical preparation of students for development creative abilities of primary school children and concretized in detail their semantic nature. Conclusions were made regarding the relevance of mentioned aspect and it was outlined the prospects for further study. На основі аналізу науково-методичної літератури та досвіду роботи у ВНЗ у статті висвітлено актуальну проблему підготовки вчителя початкової школи до викладання математики. Виділено причини недостатньої математичної підготовки педагога означеного напряму, накреслено шляхи подальшого вдосконалення цього процесу. Автор виокремлює пріоритетні положення методико-математичної підготовки студентів до розвитку творчих здібностей молодших школярів, детально конкретизовано їх змістову сутність. Зроблено висновки стосовно актуальності заявленого аспекту, окреслено перспективи подальшого вивчення.
Keywords: mathematical preparation; elementary school teacher; students; principles